Inovasi Teknologi Komunikasi dan Informasi (ICT) sebagai Alat Strategis dalam Perencanaan Organisasi Modern - Ritonga, Sonia; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Innovation in Information and Communication Technology (ICT) has become the key catalyst shaping a new paradigm in modern organizations. ICT is no longer perceived merely as an administrative tool but as a strategic component that enhances decisionmaking, process efficiency, and organizational adaptability within a dynamic environment. This study aims to analyze ICT’s role as a strategic instrument in modern organizational planning and to identify its challenges and implementation strategies. The research employs a descriptive qualitative approach through a literature review of national and international accredited journals published between 2022 and 2025. Findings reveal that ICT implementation accelerates planning processes, improves cross-departmental integration, and strengthens digital resilience amid global challenges. However, limited digital literacy, resistance to change, and infrastructural disparities hinder optimal adoption. Therefore, comprehensive ICT strategies involving human resource training, innovation-oriented digital policies, and adaptive data governance are required. Ultimately, ICT serves as the foundation for building agile, collaborative, and knowledge-driven modern organizations.